Intercropping oilseed rape as a potential relay crop for enhancing the biological control of green peach aphids and aphid‐transmitted virus diseases. Issue 11 (1st November 2019) - Lai, Rongquan; Hu, Hanqing; Wu, Xiaoting; Bai, Jingjing; Gu, Gang; Bai, Jianbao; Zhou, Ting; Lin, Tianran; Zhong, Xiujin
Abstract: Tobacco viruses transmitted by green peach aphids, Myzus persicae (Sulzer) (Hemiptera: Aphididae), cause severe disease in flue‐cured tobacco, Nicotiana tabacum L. (Solanaceae), in China and throughout the world. Field experiments were conducted in 2016 and 2017 in Longyan City, Fujian Province, China, to determine whether M. persicae and aphid‐transmitted virus diseases are affected by intercropping of oilseed rape, Brassica napus L. (Brassicaceae), in tobacco fields. The results showed that, compared with those in monocultured fields, the densities of M. persicae and winged aphids in intercropped fields significantly decreased in both 2016 and 2017. In particular, the appearance of winged aphids was delayed by ca. 7 days. Moreover, the densities of Aphidius gifuensis Ashmead (Hymenoptera: Aphidiidae), a parasitoid of the aphid, significantly increased in 2016 and 2017. Accordingly, the incidence rates of aphid‐transmitted virus diseases (those caused by the cucumber mosaic virus, potato virus Y, and tobacco etch virus) significantly decreased in the intercropped fields in 2016 and 2017. Tobacco yields and monetary value significantly increased in 2016 (by 10–25 and 14–29%, respectively) and 2017 (by 17–22 and 22–34%, respectively). Consequently, our results suggest that intercropping oilseed rape in tobacco fields is a good approach to regulating and controlling aphids and tobacco mosaic viruses, for example potyvirus, and this intercropping can help control aphid‐transmitted virus diseases in tobacco. Abstract : Field experiments were conducted in Longyan City (Fujian Province, China) in 2016 and 2017 to determine whether intercropping oilseed rape, Brassica napus (Brassicaceae), in tobacco fields, Nicotiana tabacum (Solanaceae), affects Myzus persicae (Hemiptera: Aphididae) and aphid‐transmitted viral diseases. Winged aphids occurred later, incidence rates of diseases decreased, and tobacco yield and monetary value increased in intercropped fields. Our results suggest that intercropping oilseed rape in tobacco fields is a good approach to regulating and controlling aphids and their viruses.